Aliran Feminisme Modern dan Aliran Feminisme Menurut Islam - Sri Hariati (Jatiswara, 2016)
Feminism is the ideology developed by the Western Europe in order to fight for equality between the two types of people: men and women. Their goal was to demand justice and the liberation of women from the shackles of religion, culture, and other living structure. The term feminism or gender is often called, according to Dr. Mansour Fakih, no description is able to explain briefly and clearly. They want separation of gender and sex. That is, by nature do not matter but the nature of it that need attention. For them, the concept of gender that is an inherent nature of the opponent men and women who are socially and culturally constructed. For example, it is known a gentle woman, beautiful, emotional, or motherhood. While men are considered strong, rational, manly, powerful. As according to Oakley (1972) in Sex, Gender, and Society, gender differences are not biologically meaningful, and not the nature of God. Biological differences are differences in gender (sex) which is the nature of God, and therefore are permanently different. As gender is a difference in behavior (behavioral differences) between men and women, the differences are not natural or not the provisions of God, but was created by humans through social and cultural processes that long. Therefore, a gender change from time to time.